Post-exercise ketosis - Adams, Jacob Harold (Division of Physiological Sciences, 2026)
Koeslag, Noakes and Sloan (1980) showed that the plasma fuel-hormone concentrations during exercise, and the ketosis after exercise are critically development of dependent on the amount of carbohydrate consumed on the days preceding the exercise. This suggests that the development of post-exercise ketosis could be related to the liver glycogen content after exercise, especially since endurance training is known to hepatic glycogen increase concentrations and to provide immunity against post-exercise ketosis. As it is impractical and unethical to perform liver biopsies in healthy human subjects, it was decided to investigate the problem in an animal model.